Mechanistic investigations in ultrasound-induced intensification of fermentative riboflavin production. (February 2020) - Batghare, Amit H.; Roy, Kuldeep; Khaire, Kaustubh C.; Moholkar, Vijayanand S.
Abstract: This paper reports mechanistic studies in ultrasound-assisted riboflavin production by wild strain of D. hansenii var. hansenii . Statistical optimization of fermentation resulted in riboflavin yield of 1.8 mg/g DCW. Supplementation of medium with glycine, Fe 3+, cobalt and zinc further enhanced yield to 4.1 mg/g DCW. Intensification of fermentation by sonication (at 10% duty cycle) in four intervals of 12 h each (in total log phase of 48 h) was attempted. Sonication in final 12 h of log phase was most effective with the highest yield of 20 mg/g DCW. Kinetic analysis of the ultrasound-assisted fermentation revealed higher maximum specific growth rate of cells (0.30 h −1 ) with reduced Monod constant (5.67 g/L), indicating faster cell transport and higher substrate affinity. SDS-PAGE analysis of proteins involved in riboflavin metabolism showed overexpression of all proteins in ultrasound-assisted fermentation, which enhanced the metabolism. These results are attributed to intense microturbulence generated by sonication. Graphical abstract: Unlabelled Image Highlights: ~5× rise in Riboflavin production by D. hansenii var. hansenii with sonication Optimization of fermentation followed by sonication (33 kHz, 10% duty cycle) Marked effect of additives (glycine, Fe 3+, Co 2+ and Zn 2+ ) on yield enhancement SDS-PAGE analysis of cells reveals overexpression of enzymes in metabolic pathway. Enhanced metabolism with sonication attributed to faster cellular transport.